Determination of Cervical Metastases by Lymphoscintigraphy in Patients with Oral Cancer: A Single Institute Experience - Habib, Md Ahsan; Rahman, Quazi Billur; Mutsuddy, Pupree; Begum, Shamim MF; Sultana, Sadia; Sarker, Azmal Kabir; Nath, Khokon Kumar; Begum, Rokeya (Bangladesh Journal of Nuclear Medicine, 2019)
Background: Oral cancer is the sixth most common cancer in the world. Cervical metastasis is an important adverse prognostic factor and about 40% of the patients with oral cancer develop lymphatic metastasis. Lymphoscintigraphy is the minimally invasive method for the detection of cervical nodal metastasis. The aim of the study was to detect the lymphatic involvement with the aid of lymphoscnitigraphy in patient with oral cancer undergoing surgical procedure and to find out the accuracy of the findings with the post operative histopathological diagnosis. Patients and methods: A total of 30 patients with histologically proven oral cancer underwent lymphoscintigraphic evaluation to detect the lymphatic spread of the tumor. The findings and results of lymphoscintigraphy were compared with the postoperative histopathological diagnosis. Results: Among the 30 patients, lymphatic obstruction was observed in 19 patients of whom 15 patients had perfusion defect and 4 patients had gap defect. No lymphatic obstruction was evident in the rest 11 patients by lymphoscintigraphy. The calculated sensitivity of lymphoscintigraphy in diagnosis of cervical lymph node metastasis was 100%, specificity 78.6%, accuracy 90% and positive predictive value was 84.2% and negative predictive value was 100%. Conclusion: Lymphoscintigraphy was found to be an effective method in detecting lymph node involvement and can be used as an alternative to identify regional lymph nodes metastases pre-operatively in oral cancer patients. Thereby, it will help the surgeon to plan the extent of dissection before surgery which may decrease postoperative complications related to unnecessary extensive lymph node dissection and morbidity. Bangladesh J. Nuclear Med. 21(1): 12-15, January 2018